Pemanfaatan Platform Digital E-commerce Tiktok & Shopee Affiliate dalam Manajemen Resiko dan Ketahanan UMKM Budidaya Jangkrik dan Usaha Dimsum - Nurrahman, Syafran; Saefullah, Aep; AR, Rasmawati; Sitohang, Ronny Marthin; Syaputra, Riawan; Hakim, Melati Puspita (LPPM STIE Ganesha, 2024)
Amid declining productivity in MSMEs that leads to decreased sales profit, there is a significant threat to business owners of both large and small scales. Therefore, a strategy is needed to minimize risk management and maintain business resilience so that MSMEs can continue to operate well and achieve the appropriate profit. This issue is experienced by Mr. Jhandriansyah, the owner of a dim sum and cricket farming business in the Pondok Benda, Pamulang area, who faces challenges in marketing his cricket and dim sum products. The purpose of this research is to assist the business owner in innovating the digitalization of MSME cricket farming and dim sum production by utilizing the digital e-commerce platforms Tiktok and Shopee Affiliate. The research methods used include observation, interviews, and documentation. The conclusion drawn from this research is that utilizing the digital e-commerce platforms Tiktok and Shopee Affiliate is expected to help Mr. Jhandriansyah avoid losses and bankruptcy in cricket farming and dim sum production, as well as to enhance seller relations both domestically and internationally